STRATEGI DAN TANTANGAN PENGRAJIN LURIK KEMBANGAN DALAM MENGHADAPI PERSAINGAN USAHA INDUSTRI LURIK DI YOGYAKARTA - Wahyu Triana Sari; Syamsul Bakhri (Equilibria Pendidikan : Jurnal Ilmiah Pendidikan Ekonomi, 2017)
Abstract  Lurik Kembangan is a traditional art product of Yogyakarta. Lurik Kembangan which still survive until now made by Non-Machine Weaving Machine. The more days pass, the variety of lurik becoming more diverse and creating more various products from fabric lurik. However, business competition is getting worse because there is only a few young people who willing to work as craftsmen and the impact of industrialization in Yogyakarta resulting the craftsmen’s income decreases. Qualitative research with case study approach aims to find out the strategies and challenges of lurik craftsmen in facing strait industry competition in Yogyakarta. Validity of data obtained by triangulation of data source. The technique of data analysis is done by integrating observation data at the production place of lurik group Maju Mandiri, Interview with craftsmen, Chairman of Maju Mandiri luric group, and documentation from various sources to support information about Lurik Kembangan craftsmenship. The theory used is Karl Marx's Theory of Capitalism and Theory of Glocalization from Robertson. The results showed that the strategy of the artisans of Lurik Kembangan in facing business competition is to create product innovation; maintaining the quality of traditional lurik; and expand the scope of marketing. The challenge of the craftsmen is to maintain the Lurik Kembangan increasingly heavy because the youth choose to work in factories or other sectors; competition in the middle of Yogyakarta industrialization makes the marketing of weaving lurik become increasingly narrow; the impact of the industrialization created the class of capital owners and craftsmen.Keywords: Industry, Lurik, Strategy, Challenge